Heat and mass transport impact on MHD second‐grade fluid: A comparative analysis of fractional operators. Issue 7 (30th June 2021) - Rehman, Aziz Ur; Riaz, Muhammad Bilal; Akgül, Ali; Saeed, Syed Tauseef; Baleanu, Dumitru
Abstract: The effect of the magnetic flux plays a major role in convective flow. The process of heat transfer is accompanied by a mass transfer process; for instance, condensation, evaporation, and chemical process. Due to the applications of the heat and mass transfer combined effects in different fields, the main aim of this paper is to do a comprehensive analysis of heat and mass transfer of magnetohydrodynamic (MHD) unsteady second‐grade fluid in the presence of ramped conditions. The new governing equations of MHD second‐grade fluid have been fractionalized by means of singular and nonsingular differentiable operators. To have an accurate physical significance of imposed conditions on the geometry of second‐grade fluid, the constant concentration with ramped temperature and ramped velocity is considered. The fractional solutions of temperature, concentration, and velocity have been investigated by means of integral transform and inversion algorithm. The influence of physical parameters and flow is analyzed graphically via computational software (MATHCAD‐15). The velocity profile decreases by increasing the Prandtl number. The existence of a Prandtl number may reflect the control of the thickness and enlargement of the thermal effect.